Kebahagiaan dan Penderitaan dalam Hidup Menggereja di Era Disrupsi: Analisis Surat Filipi - Murni Hermawaty Sitanggang (JURNAL TEOLOGI GRACIA DEO, 2022)
Happiness and suffering are two popular topics that are often considered contradictory and discussed separately. As a result, there is an unbalanced understanding of the two so that not a few believers are then influenced by the wrong understanding of successful theology, the concept of the law of karma or retribution, and the philosophy of Stoicism. The author argues that suffering and happiness need to be discussed together so that a correct reflection on suffering should also include happiness and vice versa. That's why this paper aims to build a more complete thought by examining the letter Philippians, which is known as the letter of joy even though it was written in prison (which is synonymous with suffering). The method used is qualitative with a descriptive approach based on a study of the Philippians letter. The conclusion of the discussion is that because the letter of Philippians states that suffering and happiness are representations of God's grace, then we as believers should not hesitate to pursue happiness even in times of suffering.  AbstrakKebahagiaan dan penderitaan adalah dua topik populer yang seringkali dianggap saling berlawanan dan dibahas terpisah. Akibatnya muncul pemahaman yang kurang berimbang tentang keduanya sehingga tidak sedikit orang percaya yang kemudian terpengaruh dengan pemahaman yang keliru dari teologi sukses, konsep hukum karma atau retribusi, dan filsafat Stoisisme. Penulis berpendapat penderitaan dan kebahagiaan perlu dibahas bersama sehingga refleksi yang benar tentang penderitaan seharusnya memuat juga kebahagiaan, dan demikian pula sebaliknya. Itu sebabnya tulisan ini bertujuan membangun pemikiran yang lebih lengkap dengan menelaah surat Filipi, yang dikenal sebagai surat sukacita meski ditulis di dalam penjara (yang identik dengan penderitaan). Metode yang digunakan adalah kualitatif dengan pendekatan deskriptif berdasarkan kajian terhadap surat Filipi. Kesimpulan pembahasan adalah karena surat Filipi menyatakan penderitaan dan kebahagiaan adalah representasi kasih karunia Allah, maka kita sebagai orang percaya tidak perlu ragu mengejar kebahagiaan bahkan di saat menderita.